Determining When Objects Die to Improve Garbage Collection - Ricci, Nathan. (2017)
Abstract: Although garbage collection frees programmers from the burden of manually freeing objects that will no longer be used, and eliminates many common programming errors, it can come with a significant performance penalty. This penalty can become particularly great when memory is constrained. This thesis introduces two pieces of work to address this problem. The first is Elephant Tracks, a tool that uses novel techniques to measure memory properties of Java programs Elephant Tracks is novel in that it places object death events more accurately than any existing tool, and is able to do so with out modification to the underlying VM. The second is the Deferred Garbage collector. Built based on observations from the Elephant Tracks traces, the Deferred Garbage Collector reduces redundant work performed by the garbage collector In this thesis, we show that the techniques used by the Deferred Collector can reduce garbage collector tracing workload in some programs.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Computer Science.; Advisor: Samuel Guyer.; Committee: Samuel Guyer, Norman Ramsey, Alva Couch, and Mark Hempstead.; Keyword: Computer science.